Germline variant of CTC1 gene in a patient with pulmonary fibrosis and myelodysplastic syndrome - Doubková, Martina; Vrzalová, Zuzana; Štefániková, Marianna; Červinek, Libor; Kozubík, Kateřina Staňo; Blaháková, Ivona; Pospíšilová, Šárka; Doubek, Michael (Multidisciplinary respiratory medicine, 2023)
INTRODUCTION: Telomeropathies are associated with a wide range of diseases and less common combinations of various pulmonary and extrapulmonary disorders. CASE PRESENTATION: In proband with high-risk myelodysplastic syndrome and interstitial pulmonary fibrosis, whole exome sequencing revealed a germline heterozygous variant of CTC1 gene (c.1360delG). This "frameshift" variant results in a premature stop codon and is classified as likely pathogenic/pathogenic. So far, this gene variant has been described in a heterozygous state in adult patients with hematological diseases such as idiopathic aplastic anemia or paroxysmal nocturnal hemoglobinuria, but also in interstitial pulmonary fibrosis. Described CTC1 gene variant affects telomere length and leads to telomeropathies. CONCLUSIONS: In our case report, we describe a rare case of coincidence of pulmonary fibrosis and hematological malignancy caused by a germline gene mutation in CTC1. Lung diseases and hematologic malignancies associated with short telomeres do not respond well to standard treatment.
Keywords: myelodysplastic syndrome; interstitial pulmonary fibrosis; CTC1 gene